Exploring the approaches towards support of academic entrepreneurship: evidence from an emerging market - Zinecker, Marek; Pěnčík, Jan; Kocmanová, Alena; Meluzín, Tomáš; Balcerzak, Adam P.; Pietrzak, Michał Bernard (Technological and Economic Development of Economy, 2024)
Over the past three decades, an exponentially growing body on elements and actors of the concept of an entrepreneurial university has emerged. Compared to its western European counterparts, however, the idea of the third role of the university has only recently been implemented in Central and Eastern European countries, and thus both research and entrepreneurial practice grapple with empirical results. In this paper, we attempt to fill this gap while adopting a case study approach to examine the issue of what resources a prominent technical university operating in the emerging market of the Czech Republic transfers to academic ventures to utilise and commercialise university research results. Within a survey, nine academic founders and two university representatives were interviewed to assess the role of university resources in facilitating academic entrepreneurship. Our research results suggest that creating infrastructure to foster the third role of universities in an emerging market is a complex and long-term issue. Formal institutions embedded in the intra-university organisational structure, such as knowledge transfer offices and entrepreneurial centres, need to be equipped with sufficient resources and competences. Skilled people with their own network of contacts to intra-university departments and external environment represented by regional incubators, venture capital providers, business angel associations, and experienced entrepreneurs should be involved in the process of creating and increasing capacity. Furthermore, the upcoming agenda should undoubtedly acknowledge the significant role of entrepreneurship education with a focus on talent recognition and entrepreneurship training to impact the entrepreneurial intentions of researchers and students. Overall, we also conclude that the motivation of academics to commercialise their inventions could be positively affected by the applied concepts of assessing their performance. Finally, this study shows that measures at all management levels have to be adopted to create a vital organisational culture that will be in alignment with the vision of entrepreneurial university. The novelty of this paper is twofold. First, the study provides a useful methodological concept of data collection as the multi-level approach was applied for studying the phenomenon of entrepreneurial university. Furthermore, the research findings have valuable implications for university authorities, as well as national and local policy makers, in creating growth programmes and supporting the entrepreneurial mindset.